ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN TRIAGE PERAWAT PELAKSANADI RUANG IGD RUMAH SAKIT TIPE C MALANG - Sova Evie; Titin Andri Wihastuti; Tony Suharsono (Jurnal Ilmiah Kesehatan Keperawatan, 2016)
Triage was important to allow quick and precise identification with every patient arriving at the emergency room, in order to avoid exacerbating the patient's condition on emergency care. So that patients with critical conditions will be given priority compared to patients with stable condition. Triage nurse is the first to receive patients in the emergency room, this interaction affects all patients in the ER and be very important on the condition number of patient visits that much. The purpose of this research is to analyze the factors associated with the implementation of triage by nurses in ER Hospital Type C Malang.This study uses comparative analytic design with cross sectional approach. Using total sampling against the 35 sample period  May 2, 2016 -  May 26, 2016. The results of the bivariate analysis of unknown factors related to the implementation of the triage nurse is the factor of emergency training (p value = 0.021). Improve skills of emergency nurses  through education and training and training in emergency triage standardized. Keywords: Training, implementation triage